2020
DOI: 10.1038/s41388-020-1379-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MAPK7/MMP9 axis for metastasis in primary bone cancer

Abstract: Metastasis is the leading cause of cancer-related death. This multistage process involves contribution from both tumour cells and the tumour stroma to release metastatic cells into the circulation. Circulating tumour cells (CTCs) survive circulatory cytotoxicity, extravasate and colonise secondary sites effecting metastatic outcome. Reprogramming the transcriptomic landscape is a metastatic hallmark, but detecting underlying master regulators that drive pathological gene expression is a key challenge, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Furthermore, grade 3 and grade 4 tumours exhibited a greater proportion of tissues with the highest levels of ERK5 expression ( Figure 4 C). These findings are consistent with recent studies that have identified a key role for ERK5 dysregulation in other cancers [ 6 , 7 , 8 , 9 , 10 , 11 , 19 , 20 , 39 ] and provides a compelling proof-of-concept rationale, together with our other data, to target ERK5 in high-grade brain tumours as means to augment the effectiveness of current temozolomide-based therapeutic strategies. Collectively, these data validate ERK5 as a credible therapeutic target in glioblastomas, which might portend some level of tumour-selectivity over normal healthy brain tissue.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, grade 3 and grade 4 tumours exhibited a greater proportion of tissues with the highest levels of ERK5 expression ( Figure 4 C). These findings are consistent with recent studies that have identified a key role for ERK5 dysregulation in other cancers [ 6 , 7 , 8 , 9 , 10 , 11 , 19 , 20 , 39 ] and provides a compelling proof-of-concept rationale, together with our other data, to target ERK5 in high-grade brain tumours as means to augment the effectiveness of current temozolomide-based therapeutic strategies. Collectively, these data validate ERK5 as a credible therapeutic target in glioblastomas, which might portend some level of tumour-selectivity over normal healthy brain tissue.…”
Section: Resultssupporting
confidence: 92%
“…Of particular interest amongst the putative hits identified within this screen was ERK5 (also known as MAPK7 and MEK5), as it has recently been identified as a potential oncogenic factor in several other cancers [ 6 , 7 , 8 , 9 , 10 , 11 , 18 , 19 , 20 ], and several potential therapeutic small molecule inhibitors have recently been developed [ 12 , 13 , 14 , 15 , 21 ]. To further validate ERK5 as promoting TMZ resistance in glioma cells and to discount potential off-target RNAi effects, we used siPOOLs consisting of 30 individual low nM siRNA that have been shown to give effective knockdown at low total nM concentrations ( Figure S1B ) with reduced off-target effects [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Green [47] demonstrated that MAPK7 is a master regulator of MMP9 and promotes the formation of metastasis. Indeed, we observed a dysregulation in MAPK signaling at the protein level when comparing Fusobacteriales -high vs. -low patients of the TCGA-COAD-READ cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed a dysregulation in MAPK signaling at the protein level when comparing Fusobacteriales -high vs. -low patients of the TCGA-COAD-READ cohort. MAPK7 induces EMT transition, cell migration and regulates TAMs polarization in a metallo proteins-dependent manner [47], rendering it an appealing upstream therapeutic target. IL6 orchestrates MAPK-STAT3 signaling which in turn regulates the dynamic transition between 2 CAFs sub-populations, EMT-CAFs and proliferation-CAFs [48], rendering the IL6-TGFβ-EMT-CAFs cross-talk a valid therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The P2RX7B expressing OS cells when stimulated with the potent P2RX7 agonist BzATP, demonstrated increased invasion and migration rates. Invasion requires the expression of various matrix metalloproteinases (MMPs) that are capable of digesting the ECM, allowing the cells to break away from the primary site and interact with tumour-associated stromal cells such as macrophages 47 . Activation of P2RX7 has been shown to induce the release of MMP13 in breast cancer cells 46 and has long been known to be responsible for the ATP-induced rapid release of MMP-9 from human peripheral-blood mononuclear cells 48 .…”
Section: Discussionmentioning
confidence: 99%